Gender Equality in the Labor Market: Women's Employment and Earnings - Janet Gornick (Luxembourg Income Study (LIS), 1999)
This chapter presents a cross-national portrait of gender equality in the labor market in the early 1990s, based on Luxembourg Income Study (LIS) data from fifteen countries. Cross-country comparisons are analyzed in the context of variation both across, and within, the three welfare state regime types that have dominated recent theoretical and empirical scholarship on the welfare state. The social democratic welfare states are represented in this analysis by Denmark, Finland, Norway, and Sweden; the conservative (or corporatist) welfare states, by Belgium, France, Germany, Italy, Luxembourg, the Netherlands, and Spain; and the liberal (or residual) welfare states include, here, Australia, Canada, the United Kingdom, and the United States. The question as to whether these three regime types shape gendered labor market outcomes - in other words, the extent to which variation across the regime types is greater than variation within them - anchors the presentation of empirical findings. In the next section, three central concerns about the meaning of gender equality in the labor market are raised, and resolutions discussed. The following section traces major trends in gendered labor market patterns since 1960. Two subsequent sections present empirical results for the 1990s on gender differences across various labor market outcomes. Policy implications are presented in the final section, followed by conclusions.
Keywords: 330; Weibliche Arbeitskräfte; Arbeitsmarkt; Lohn; Vergleich; Geschlecht; Industrieländer